MYXOSPOREASIS PADA IKAN KOI (Cyprinuscarpio) - Novia Christi Prihartini; Alfiyah Alfiyah (Faculty of Science and Technology University Ibrahimy, 2017)
Myxosporeasis disease caused by phylum Myxozoa are obligate parasites that many dominates in freshwater. Myxozoa easily recognizable by their multicellular spores which have a typical polar capsules, and has a considerable number of species (more than 1350 species) mainly from class Myxosporea. The life cycle of this parasite occurs horizontally (indirect) involving an invertebrate (Oligochaeta) and a vertebrate host (fish or amphibians). The development of this species is quite rapidly over the last 30 years, especially in the sectors of aquaculture, andhave also been recognized as commercially important pathogen of fish, because it can cause severe economic losses in cultured fisheries. In Indonesia, Myxobolus sp.reportedly attacked various freshwater species, one of them in the cultivation of carp, because it caused the death of 60-90% of the population infected fish. The impact of the infestation Myxobolus sp. dependent on investation level and location of the cyst.Large infestations that occurred in the gills causing tissue death (necrosis) and dysfunctional breathing. Infections that occur in the intestine, will cause myoliticin the intestinal wall. The purpose of this study was to look investing parasites also macroscopic (anatomic pathology) and microscopic (histhopathological) in tissues of infected Myxobolus sp. The method of research is descriptive. Koi sample used with a length of 6-8 cm and comes from Nglegok, Blitar. Subsequently, samples were examined clinically, and are selected which produce nodules 1-4 (mild infection) and which have more than 8 nodules (severe infection) on the gills. Results of macroscopic observation showed swelling in the gills because of their reddish white nodules. In addition, the gills look pale red. Whereas in histopathology, Koi infected with spores Myxobolus sp.indicate the occurrence of fusion, congestion, hyperplasia, necrosis, inflammation and edema.